Dynamic performance analysis of a 3.3 kV SiC MOSFET half-bridge module with parallel chips and body-diode freewheeling - Hussein, Abdallah; Mouawad, Bassem; Castellazzi, Alberto (2018)
Recently, 3.3 and 6.5 kV power MOSFETs have been introduced. Based on the 3.3 kV device, a 100 A half-bridge power module has been developed, using parallel chips for current scaling and relying exclusively on the use of the transistors body-diode for current free-wheeling (i.e., no antiparallel external diode chips are used). This paper presents a thorough parametric characterization of the module switching performance. Single-chip and parallel-chip operation are investigated in both double-pulsea type tests and realistic singlephase inverter operation.